Intimate Partner Victimization and Depressive Symptoms: Approaching Causal Inference Using a Longitudinal Twin Design - Connolly, Eric J. (Journal of quantitative criminology, 2022)
Objectives While a wealth of research reports a robust association between intimate partner victimization and depression, the relationship has not been tested using twin-based research designs to control for unmeasured genetic and shared environmental confounding. Methods Twin data from the National Longitudinal Study of Adolescent to Adult Health are analyzed to test the causal hypothesis that intimate partner victimization increases depressive symptoms across the life course. A series of twin-based research methodologies are used to examine whether twin differences in intimate partner victimization during late adolescence are associated with differences in depressive symptoms in young adulthood. Results Males and females did not significantly differ in their prevalence or frequency of reported intimate partner victimization during late adolescence. Genetic and nonshared environmental effects were found to account for the covariance between intimate partner victimization and depressive symptoms. After controlling for common genetic effects, within-twin pair differences in intimate partner victimization were positively associated with within-twin pair differences in depressive symptomatology. Conclusions The results offer further support for the mental health consequences associated with intimate partner victimization and help strengthen causal inference arguments for the relationship between intimate partner victimization and depressive symptoms later in life.